Analysis on the Development of Hannibal Lecter’s Psychology from a Teenager until an Adult as Depicted in Hannibal Rising and Silence of the Lambs by Thomas Harris - Nur Nindya Kirana (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
This paper is a form of analysis towards the psychology of fictional character Hannibal Lecter since he was a teenager until he becomes an adult. The aspect which becomes the very focus of this research paper is Self-Defense Mechanism that Hannibal Lecter is going through in his life. Furthermore, this paper has three important objectives; which are describing Hannibal Lecter‟s early chilhood‟s background, presenting as well as analyzing the psychology of young Hannibal Lecter after getting through severe traumatic experience, and analyzing the psychology of mature Hannibal Lecter as a psychiatrist as well as a murderer. The approach used to complete this paper are qualitative and psychological approach. In addition, to collect the data, library research methodology is applied. The result of this study indicates that Hannibal Lecter undergoes several Self-Defense Mechanism in his teenage years which are Repression, Projection and Regression as well as Post-Traumatic Stress Disorder (PTSD). Lastly, it can be concluded that Hannibal Lecter still undergoes Self-Defense Mechanism which is Sublimation even though he has grown to be a mature adult. Keywords: self-defense mechanism, repression, projection, regression, sublimation